Systematic profiling of alternative splicing in Helicobacter pylori-negative gastric cancer and their clinical significance - Chuan Liu; Chuan Hu; Zhi Li; Jing Feng; Jiale Huang; Bowen Yang; Ti Wen (Cancer Cell International, 2020)
Abstract Background Alternative splicing (AS) may cause structural and functional variations in the protein to promote the proliferation of tumor cells. However, there is no comprehensive analysis of the clinical significance of AS in Helicobacter pylori-negative gastric cancer (HP − GC). Methods The clinical, gene expression profile data and AS events of 138 HP − GC patients were obtained from the database named the cancer genome atlas. Differently expressed AS (DEAS) events were determined by a comparison of the PSI values between HP − GC samples and adjacent normal samples. Unsupervised clustering analysis, proportional regression and Kaplan–Meier analysis were used to explore the association between clinical data and immune features and to establish two nomograms about the prognosis of HP − GC. Finally, splicing networks were constructed using Cytoscape. Results A total of 48141 AS events and 1041 DEAS events were found in HP − GC. Various functions and pathways of DEAS events parent genes were enriched, such as cell-substrate junction, cell leading edge, focal adhension, and AMPK signaling. Seven overall survival (OS)-related and seven disease-free survival (DFS)-related AS events were used to construct the prognostic signatures. Based on the independent prognostic factors, two nomograms were established and showed excellent performance. Then, splicing regulatory networks among the correlations suggested that splicing factors were significantly associated with prognostic DEASs. Finally, the unsupervised clustering analysis revealed that DEAS-based clusters were associated with clinical characteristics, tumor microenvironment, tumor mutation burden, and immune features. Conclusion Seven OS-related and seven DFS-related AS events have been found to be correlated with the prognosis of HP − GC and can be used as prognostic factors to establish an effective nomogram.